Imagining their Future Selves: Children's Attitudes to Older People and their Expectations of Life at Age 70. (3rd July 2018) - Lloyd, Katrina; Devine, Paula; Carney, Gemma M.
Abstract : Studies eliciting the views of children on ageing are rare, particularly those that focus on imagining a future self as an 'old' person and how this might be linked to current attitudes to older people. To address this gap, 2, 365 children participated in an online survey which included questions on ageing. Findings suggest that children who hold negative views about old people visualise poorer outcomes for themselves at age 70. Implications of the findings are discussed in the context of an ageing population and the need to develop strategies to prevent the formation of prejudices against older people from an early age.